1999
DOI: 10.1046/j.1365-2389.1999.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil chemistry accompanying acidification over more than 100 years under woodland and grass at Rothamsted Experimental Station, UK

Abstract: Summary We have examined the effect that acid deposition and other sources of acidity have had over the last 110–140 years on soil under woodland (Broadbalk and Geescroft Wildernesses) and grassland (Park Grass) comprising some of the Classical Experiments at Rothamsted Experimental Station. Changes in soil chemistry have been followed by analysing some of the unique archive of stored samples for pH, water‐soluble and exchangeable base cations, aluminium, iron and manganese, exchangeable acidity, cation exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
104
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 24 publications
(37 reference statements)
15
104
0
Order By: Relevance
“…It has been shown that changes in soil reaction during succession depend on initial pH. Thus, acidification during succession varies according to soil type and initial buffering capacity (Blake et al 1999;García et al 2007) and only a slow decline in soil reaction on soils with high buffering capacity (like our study site) is expected (Leuschner and Gerlach 2000). The decreasing amount of phosphorus in the soil indicates accumulation of phosphorus in the living plant biomass.…”
Section: Effects Of Successional Changes On Soil Chemical Properties mentioning
confidence: 74%
“…It has been shown that changes in soil reaction during succession depend on initial pH. Thus, acidification during succession varies according to soil type and initial buffering capacity (Blake et al 1999;García et al 2007) and only a slow decline in soil reaction on soils with high buffering capacity (like our study site) is expected (Leuschner and Gerlach 2000). The decreasing amount of phosphorus in the soil indicates accumulation of phosphorus in the living plant biomass.…”
Section: Effects Of Successional Changes On Soil Chemical Properties mentioning
confidence: 74%
“…On the other hand, lowering the pH of carbonate-containing soils would, to some degree, improve their quality and thus increase the vegetation cover and biological productivity (Lieb et al, 2011;Yang et al, 2012). In the non-carbonate-containing soils, an increase in soil acidity may reduce availability of some nutrient cations, such as Ca and Mg, and enhance availability of some toxic cations, such as aluminum (Al) and manganese (Mn), which might limit plant growth and increase susceptibility to low temperature, drought and herbivory stress in these ecosystems (Blake et al, 1999;Lieb et al, 2011;Chen et al, 2013).…”
Section: Soil Phbc and Potential Consequences Of Soil Acidificationmentioning
confidence: 99%
“…However, in recent decades, various anthropogenic activities have accelerated soil acidification to a great extent. Acid deposition resulting from air pollution is a major cause for increased soil acidity (Reuss and Johnson, 1986;Blake et al, 1999). At present, acid deposition is still a serious factor that accelerates soil acidification in China (Vogt et al, 2006;Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%